Establishment of A New HBV Cell Culture Model by Covalently Closed Circular DNA Direct Transfect. Issue 3 (January 2021) - Zhao, Zhonghua; Tang, Yuwei; Wei, Qinglv; Zhang, Huatang
Abstract: Hepatitis B virus (HBV) infection is a public health problem in China and worldwide. Covalently closed circular DNA (cccDNA) is the template for HBV replication and exists stably in hepatocytes, which is the main factor for persistent HBV infection and the key target for the cure of HBV infection. The establishment of a suitable cell model is helpful to research the HBV pathogenesis and antiviral drug screening. We have established a new cell culture model of HBV infection by direct transfect of cccDNA, which provides a practical model for further research of HBV virology and antiviral drug development.